Transcripts: Going through a phase - Samuelsson, Robin (Uppsala University, 2020)
Transcripts (in Swedish) of teacher students participating in a teaching sequence on phase transition and energy transfer.

The dataset was originally published in DiVA and moved to SND in 2024.

Transkriptioner (på svenska) av lärarstudenter som deltar i en undervisningssekvens om fasövergång och energiöverföring.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Transcripts: Going through a phase
Keywords: teaching profession; undervisningsarbete; energy transfer; energiöverföring; Physics with specialization in Physics Education; Fysik med inriktning mot fysikens didaktik; Other Physics Topics; Annan fysik; Educational Sciences; Utbildningsvetenskap